Makna Ritual Tolak Bala Ghatib Beghanyut bagi Masyarakat di Kelurahan Kampung Dalam Kabupaten Siak Provinsi Riau - Egri Jayanti; Fitri Eriyanti (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The rapid development of modernization has an impact on the erosion of the values ​​of the ritual of rejecting bala ghatib beghanyut as a Malay cultural tradition so that it needs to be preserved through deeper study and meaning. The aim of the research is to analyze the meaning and function of the ritual of rejecting bala ghatib beghanyut for the community in Kampung Dalam Village, Siak Regency. The research method uses descriptive qualitative with data collection through enotography and interviews. The research results show the symbolic meaning of the ghatib beghanyut ritual as an identity and tradition passed down from generations to ancestors as well as a means of implementing Islamic values ​​and avoiding danger. The function of the ghatib beghanyut banishment ritual tradition is as a religious function, social function, economic function, and as a medium for treatment in society.